(untitled) (University Journal of Zoology, Rajshahi University, 2008)
An investigation was made on the parasitic infestation of an indigenous major carp, Labeo rohita collected from different water bodies of Rajshahi district during April 2006 to January 2007. A total of 70 host fishes were examined during the study period of which 55 fishes were found infected by numerous protozoan and metazoan parasites. In all 2348 parasites belonging to eight genera were recorded from the surveyed hosts. Among them six were ectoparasites (Trichodina, Myxobolus Chilodonella, Dactylogyrus, Gyrodactylus and Argulus) and two were endoparasite (Eucreadium and Camallanus). The infestation exhibited monthly or seasonal fluctuation, the maximum abundance of parasites was recorded in the month of December and the minimum in July. It was observed that the infection was the maximum in pre-winter to winter and the minimum in the rainy season. Prevalence, intensity and abundance of the infestation were also found to be related to different length group of the hosts, the medium sized fishes were more infested and the larger size fishes were less infested while the smaller size fishes showed medium infestation. Key words: Parasite, L. rohita, prevalence, intensity, abundance Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 31-34